Clinical profile and complication of nephrotic syndrome in a tertiary health care center in central India - Agrawal, Avyact; Singh, Ravi Prakash (Indian Journal of Child Health, 2020)
Background: Nephrotic syndrome (NS) is a common renal disease that is characterized by episodes of relapses and remissions, with variations in the outcome. It is an important cause of chronic renal disease. Objective: The objective of the study was to access the clinical presentation, investigation profile, associated complication, and therapeutic response in children with NS. Materials and Methods: This prospective observational study was conducted from March 2017 to June 2018 in the department of pediatrics of a tertiary care institution of Central India. A total of 107 children diagnosed with NS were included in the study. Detailed information on age, sex, age at first episode, presenting complaint, history of presenting illness, social, and family history was taken. Detailed general physical examination, systemic examination, investigation profile, and response to management were recorded on a pro forma and correlated statistically. Results: of 107 cases of NS, the most common age group was 5–7 years (54.2%). There were 73 (68.2%) males and 34 (31.7%) females with a male-to-female ratio of 2.1:1. It was found that 39 (36.4%) subjects were newly diagnosed and 68 (63.6%) were relapse cases. A total of 95 (88.8%) patients were steroid-sensitive while 12 (11.2%) had initial steroid resistance NS. Conclusion: In our study, clinical presentation and response to treatment in cases with NS did not differ significantly from other studies.